2007
DOI: 10.1139/w07-028
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of fatty acid in yeast: addition of reducing agents to the reaction medium influences β-oxidation activities, γ-decalactone production, and cell ultrastructure inSporidiobolus ruineniicultivated on ricinoleic acid methyl ester

Abstract: The sensitivity of Sporidiobolus ruinenii yeast to the use of reducing agents, reflected in changes in the oxidoreduction potential at pH 7 (Eh7) environment, ricinoleic acid methyl ester catabolism, gamma-decalactone synthesis, cofactor level, beta-oxidation activity, and ultrastructure of the cell, was studied. Three environmental conditions (corresponding to oxidative, neutral, and reducing conditions) were fixed with the use of air or air and reducing agents (hydrogen and dithiothreitol). Lowering Eh7 to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…Similarly, during chronological aging of S. cerevisiae culture, the survival was directly correlated to the decrease of glycogen and trehalose contents of yeast (Samokhvalov et al 2004). Moreover, previous observations showed modifications of yeast cell size, morphology and ultra-structure in gaseous environments (Feron et al 2007;Pham et al 2007a). In particular modifications of the cell wall were observed.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Similarly, during chronological aging of S. cerevisiae culture, the survival was directly correlated to the decrease of glycogen and trehalose contents of yeast (Samokhvalov et al 2004). Moreover, previous observations showed modifications of yeast cell size, morphology and ultra-structure in gaseous environments (Feron et al 2007;Pham et al 2007a). In particular modifications of the cell wall were observed.…”
Section: Discussionmentioning
confidence: 72%
“…It was not the case for the trehalose content which was influenced mainly by the redox environment. A modification of external redox potential can affect the physiology of microorganism by altering membrane structure and properties (permeability, potential) (Riondet et al 1999;Kirakosyan et al 2004) as well as the internal redox state (Feron et al 2007;Pham et al 2007b). Thus, in our case, it seems likely that gas-in culture conditions, especially with O 2 and H 2 , correspond to conditions of stress for yeast cells, leading to accumulation of storage substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2002), Yarrowia lipolytica (Husson et al. 2006) and more recently Sporidiobolus ruinenii (Feron et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, few studies have described the influence of redox environment on physiology of S. cerevisiae , Yarrowia lipolytica (Husson et al 2006) and more recently Sporidiobolus ruinenii (Feron et al 2007). Husson et al (2006) showed that reducing conditions were favourable to hydroperoxide lyase (HPL) synthesis as well as its activity but it was unfavourable to yeast growth.…”
Section: Introductionmentioning
confidence: 99%